Penguatan Pembelajaran Berbasis Blended Learning Pada Masa Pandemi: Kajian Konseptual - Rinda Fauzian; Muhammad Gufron Fauzi (Peneliti.net, 2021)
Learning during a pandemic is required to be effective and efficient. Blended learning is a tool to achieve the effectiveness and efficiency of learning. The purpose of this study is to analyze the characteristics of blended learning, its implementation and implications for the effectiveness and efficiency of learning during the pandemic. strengthening blended learning-based learning during the pandemic. The research method used is library research (library research). The data is taken from scientific sources with qualitative data analysis, so that the data provides accurate information. The results showed that blended learning-based learning during the pandemic had positive implications on the effectiveness and efficiency of pandemic-based learning. These positive attitudes include: independent, problem solving and collaborative. If analyzed, blended learning-based learning during the pandemic greatly strengthens the effectiveness and efficiency of learning during the pandemic.